Aqueous intralesional bleomycin sclerotherapy in lymphatic malformation: Our experience with children and adult - Bhatnagar, Ankur (Natl J Maxillofac Surg, 2017)
OBJECTIVES: Lymphatic malformations (LMs) are aberrant proliferation of sequestrated lymphatic vessels during early embryogenesis and do not communicate directly with the general lymphatic system. The absence of vascular flow is the hallmark of LMs and is usually symptomless apart from painless disfiguring mass with concerns regarding cosmesis. DESIGN: Sclerotherapy has gained prominence as a preferred treatment modality for macrocystic lesions. Here, we present our experience with use of aqueous bleomycin as intralesional sclerosing agent, an economical first-line treatment for macrocystic variant of LMs in children and adults. While bleomycin microsphere in oil has been commonly used in many previous studies, we have used aqueous bleomycin solution as the sclerosing modality which is easily available and economical. MATERIALS AND METHODS: Twenty-seven patients of macrocystic LM including adults and children underwent bleomycin sclerotherapy under ultrasonography guidance. Number of sessions, dose administered, and the response to therapy along with all side effects were noted. RESULTS: Sixteen patients received 3 or less sessions while rest needed 4–6 sessions of sclerotherapy for desired response. The response was excellent in 22 patients while 5 patients showed good response. Eleven patients developed minor side effects in form of fever, local infection, intracystic bleed, and local skin discoloration. Postsclerotherapy, surgery was performed in two patients. CONCLUSION: The better response in the present study can be attributed to targeting of individual cysts in multiloculated lesion, ultrasound-guided aspiration of the cysts content before drug delivery, and postprocedure compression which increases the contact time between cyst wall and bleomycin reducing the chances of postprocedure seroma formation. Since the drug acts on the endothelial lining of the cyst, volume of the cyst is the major determinant in response. Aqueous bleomycin had comparable results with oil-based microsphere establishing it as an economical alternative treatment modality.